Chemical composition of essential oil and hexane extract and antioxidant activity of various extracts of Acmella uliginosa (Sw.) Cass flowers from Indonesia - Maimulyanti, Askal; Prihadi, Anton Restu (Agriculture and Natural Resources, 2016)
Medicinal plants are rich sources of natural antioxidant which are used in the prevention and treatment of disease like artherosclerosis, heart stroke, diabetes and cancer and to delay the process of aging. Acmella uliginosa (Sw.) Cass is an edible herb traditionally used in the treatment of many diseases. Analysis of volatile components in the flower extract used gas chromatography-mass spectrometry. The results showed the main components of the essential oil were caryophyllene (21.27%), caryophyllene oxide (15.49%), and 3-carene (10.73%). The main components of the hexane extract were N-isobutyl- 2E,6Z,8E-decatrienamide (37.80%), a-pinene (4.98%) and hexadacanoic acid-methyl ester (4.78%). The antioxidant activity of A. uliginosa (Sw.) Cass flower from Indonesia was determined using 1,1, diphenyl- 2-picryl hydrazine (DPPH) free radical scavenging assay. The IC50 (defined as the total antioxidant necessary to decrease the initial DPPH radical by 50%) of extracts was calculated. A comparative study determined that A. uliginosa (Sw.) Cass in methanol extract showed higher antioxidant potential (IC50 ¼ 96.83 mg/mL) compared to ethyl acetate extract (IC50 ¼ 123.46 mg/mL) and n-hexane extract (905.92 mg/mL) against DPPH free radicals.